Analisis Pemasaran Gabah (Studi Kasus: Desa Serdang, Kecamatan Beringin, Kabupaten Deli Serdang) - Sri Leli Sitorus; Khairul Saleh; Mitra Musika Lubis (Universitas Medan Area, 2019)
This study aimed to determine the grain marketing channels in Desa Serdang, Kecamatan Beringin, Deli Serdang and to determine the efficiency of grain marketing in Serdang Beringin Subdistrict, Deli Serdang regency. Farmers sampling was conducted using proportionate stratified random sampling 53 farmers. While traders Sampel taken by the census method that was as much as three merchants and traders to take as much refinery in three traders with purposive sampling method. Beringin the total number of samples in this study was 59 samples. The results showed that there were two channels of grain marketing research location that was, the first channel starts from farmers to traders refinery in District Beringin. The second channel starts from farmers, collectors next to the refinery merchant Beringin Subdistrict. The marketing margin was Rp. 4.500 contained in the channel I and the channel more efficient contained in the channel II with the value of an efficiency of 12,61%.